131‐Oxophorbine protopheophorbide A from Ziziphus lotus as a novel mesenchymal‐epithelial transition factor receptor inhibitory lead for the control of breast tumor growth in vitro and in vivo. Issue 11 (18th July 2018) - Souid, Soumaya; Elsayed, Heba E.; Ebrahim, Hassan Y.; Mohyeldin, Mohamed M.; Siddique, Abu Bakar; Karoui, Habib; El Sayed, Khalid A.; Essafi‐Benkhadir, Khadija
Abstract : The failure of chemotherapy especially in triple negative breast cancer (TNBC) patients has been correlated with the overexpression of the mesenchymal‐epithelial transition factor (c‐Met) receptor. Thus, the hepatocyte growth factor (HGF)/c‐Met signaling axis has gained considerable attention as a valid molecular target for breast cancer therapy. This study reports for the first time the discovery of the 13 1 ‐oxophorbines pheophorbide A and protopheophorbide A along with chlorophyllide A from Ziziphus lotus, an edible typical Tunisian plant, as the potent antiproliferative compounds against the human breast cancer cells MDA‐MB‐231 and MCF‐7. Compared to other compounds, protopheophorbide A exerted the highest light‐independent antiproliferative effect against the metastatic TNBC MDA‐MB‐231 cells (IC50 = 6.5 μM). In silico, this compound targeted the kinase domain of multiple c‐Met crystal structures. It potently inhibited the kinase domain phosphorylation of wild and mutant c‐Met in Z‐LYTE kinase assay. Protopheophorbide A inhibited HGF‐induced downstream c‐Met‐dependent cell proliferation, survival, adhesion and migration through RAF/MEK/ERK and PI3K/PTEN/AKT signaling pathways modulation, ROS generation and activation of JNK and p38 pathways. Interestingly, this compound impaired the ability of the MDA‐MB‐231 cells to adhere at different extracellular matrix proteins by reducing the HGF‐induced expression of integrins αv, β3, α2, and β1. Moreover, protopheophorbide A exhibited anti‐migratory properties (IC50 = 2.2 μM) through impacting the expression levels of E‐cadherin, vimentin, β‐catenin, FAK, Brk, Rac, and Src proteins. Importantly, treatment with protopheophorbide A significantly inhibited the MDA‐MB‐231 tumor growth in vivo. Our results suggest that protopheophorbide A could be a novel c‐Met inhibitory lead with promise to control c‐Met/HGF‐dependent breast malignancies.